Design of Multimodal Transport Information Service System Based on Space-Based Internet of Things - Yangyang LU; Guangyue XUE; Hanchang SUN; Qingxia XIE (天地一体化信息网络)
With the statement of container multimodal transport development tendency and network bottleneck hindering information and intelligence evolution, an open, neutral, safe, and credible multimodal transport information service platform based on spaced internet of things and big data technologies was introduced.This platform can provide container tracking, supervision and other comprehensive application services for diff erent freighters such as railway, road, water and air transportation etc., effectively improving the efficiency of multimodal transport service.The platform will bring vital economic and social benefi ts and provide support for establishing modern logistics system.